GAINING PUBLIC TRUST THROUGH DIGITAL MEDIA BY PUBLIC RELATIONS OF THE GOVERNMENT OF SLEMAN YOGYAKARTA - Riski Apriliani (Profetik: Jurnal Komunikasi, 2022)
This study intends to describe the efforts of the District Government Public Relations. Sleman in building public trust in dealing with the COVID-19 pandemic situation. Hoax information results in a decrease in public trust in the government because there is a lot of miss information related to COVID-19 and miss information related to government policies, causing a crisis of trust. Therefore, Government Public Relations has the main task of conveying true information and must be able to build public trust and deal with crisis situations. This type of research is descriptive research with a qualitative approach. Data collection techniques were carried out by in-depth interviews with the Public Relations of the District Government. Sleman and literature study. The concept of Public Relations (Cutlip & Center) and the Dimensions of Public Trust (Rawlins) help researchers to explain public relations efforts to build public trust during the COVID-19 pandemic. The results showed that the Public Relations of the District Government. Sleman has been in building public trust and fighting hoaxes by providing fast information through online media, delivering clear, consistent messages and coordinating efforts to build trust. Nevertheless, the researcher considers the efforts to build public trust carried out by the Public Relations of the District Government. Sleman is not yet fully maximized. This is because there is no clear measurement by the Public Relations of the District Government. Sleman to evaluate performance and efforts to build trust in the community regarding the COVID-19 pandemic.